Agroteknologi Konservasi untuk Meningkatkan Kualitas Tanah dan Produktivitas Kentang di Kabupaten Kerinci Provinsi Jambi (Agrotechnology Conservation To Improve Soil Quality and Potatoes Productivity In Kerinci District, Jambi Provinci) - Henny H.; Itang Ahmad Mahbub; . Arzita (Bioplantae, 2013)
Potato is a prime horticultural commodities for Kerinci District with production centers in the volcanic highlands of Kerinci Mount, Jambi Province. Less of physical and chemical properties of the soil, excessive fertilizers and pesticides chemical were caused potato low productivity anddeclined soil quality. The objectives of this research were to determine the potato agrotechnology that can improve soil quality and potato productivity in the Sub District of Kayu Aro, Kerinci District, Jambi Province. Potato agrotechnology were studied through small of experimental plots in Gunung Labu Village by a randomized block design with 13 treatments (agro-potato : ridges across the slope, a quality seeds, dose of lime, manure and chemical fertilizers according to the recommendations provided). Data collected include before and after of treatment of soil properties and productivity of potato. Results of the research showed that planting potatoes in ridges across the slope with 0.5 tons of Dolomite lime, 10.0 tons of manure, 150.0 kg of Urea, 150.0 kg of ZA, 25.00 kg of SP-36 and 20.00 kg KCl per hectare were sufficient to obtain optimal productivity of potato (39.52-37.0 kg/plot, equivalent 32.93-30.91 t/ha) and improved soil chemical properties of Andisol Gunung Labu Village (especially pH, base saturation and exchangeable bases) in the Western Sub District of Kayu Aro, Kerinci District .Key Words: Soil quality, agrotechnology